Rapid population decline in migratory shorebirds relying on Yellow Sea tidal mudflats as stopover sites - Colin E. Studds; Bruce E. Kendall; Nicholas J. Murray; Howard B. Wilson; Danny I. Rogers; Robert S. Clemens; Ken Gosbell; Chris J. Hassell; Rosalind Jessop; David S. Melville; David A. Milton; Clive D. T. Minton; et al. (Nature Communications, 2017)
Stopover sites are crucial to migratory birds, but the influence of this habitat on population dynamics has not been quantified. Here, Studds et al. show that, among ten migratory species, the degree of reliance on disappearing stopover habitat in the Yellow Sea tidal flats predicts the extent of recent population declines.